PRAWO I ETYKA W MEDYCYNIELegal consequences connected with disclosing medical records to an unauthorized person - Wroński, Konrad; Bocian, Roman; Cywiński, Jarosław; Dziki, Adam (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Regulations contained in appropriate acts impose an obligation to keep patients’ medical records on the National Health Service institutions, doctors, nurses and midwives as well. The information in the medical records is sensitive information and must be protected in such a way that an unauthorized person may not have access to it. A number of legal acts impose upon the National Health Service institutions an obligation to protect personal data collected in medical documentation. Anybody committing an offence of disclosing information about a patient’s condition will be prosecuted. The following article presents legal and penal aspects connected with the disclosure of medical records to an unauthorized person